Dental anomalies and orthodontic characteristics in patients with pseudohypoparathyroidism - Jane Hejlesen; Line Underbjerg; Hans Gjørup; Tanja Sikjaer; Lars Rejnmark; Dorte Haubek (BMC, 2019)
Abstract Background Pseudohypoparathyroidism (PHP) is a rare and inherited disease caused by mutations in the GNAS-gene or upstream of the GNAS complex locus. It is characterized by end-organ resistance to PTH, resulting in hypocalcemia and hyperphosphatemia. We aimed to investigate the dental anomalies according to tooth types and the orthodontic characteristics of patients with PHP. Methods Using a cross-sectional design, 29 patients (23 females) with PHP, living in Denmark, were included, and their clinical intraoral photos and radiographs were examined. Results Pulp calcification was found in 76% of the patients. Blunting of root apex was present in 55% and shortening of root in 48% of the examined patients. Blunting and shortening of roots were seen more often in premolars than in other tooth types (pboth < 0.01). Crowding of lower anterior teeth was frequently observed (36%) as well as diastema in the upper arch (25%), midline diastema (18%), and Class III malocclusion (11%). Conclusion In the present study population, the teeth were frequently affected by pulp calcification and/or deviation of the root morphology. Blunting and shortening of root(s) were more often seen in premolars than in other tooth types. Class III malocclusion was relatively prevalent. It is important to pay attention to dental anomalies and occlusion in order to provide adequate care for patients with PHP.